Konservasi Sumber Mata Air Dilem di Desa Papring Kelurahan Kalipuro Kabupaten Banyuwangi - Anam, Muhamad Khoirul; Qiram, Ikhwanul (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2022)
Abstract – Clean water is one of the things needed in the community because it is an important factor in the sustainability of living things. The community needs clean water that is suitable for consumption to minimize the presence of diseases that have an impact on the community. Because we as a society must maintain springs to maintain water quality. Banyuwangi Regency is one that has abundant springs, one of which is located in the source dilem of the Papring neighborhood of Klipuro Village. To maintain the quality of water sources in the papring environment, Klipuro Village, the Machine Student Association (HMM) and PGRI University Lecturers carry out community service in the form of conservation of located in Papring, Kalipuro Village, Banyuwangi Regency. Keyword : Conservation, spring water source, water quality